Preparation microcycle programs - Sidorchuk, S.; Thorev, V. (2008)
The microcycle of a training process encompasses a series of training exercises carried out within several days providing complex solution in a given stage of the preparation of sportsmen. The period of a microcycle does not help to achieve essential and long-term shifts in the organism of the sportsmen. Microcycles constitute a part of the plan in the preparation structure for the regulation of training load. In the training sessions (TS) of national and club teams of Russia, 2 to 4 days microcycles with the general number of training exercises from 4 to 10 are used. Three-day training microcycles are most characteristic (up to 60 %) followed by one rest day. The microcycles of four days account for 28 % of TS. The two-day cycles are used in 12 % of the cases only. Preparation of club teams outside of TS module is maintained with the use of training microcycles with duration of 4 to 6 working days - independent from the stage of preparation - with number of trainings from 8 to 12.